An in-depth exploration of four heterogeneity structure-based EGFR mutation subgroups in Chinese non-small cell lung cancer - Yongfeng Yu; Fei Yao; Jin Wang; Zhan Huang; Tao Hu; Changbin Zhu; Shun Lu (BMC Pulmonary Medicine)
Abstract Background EGFR mutations have been classified into four functional subgroups (Classical-like, P-loop and αC-helical compressing (PACC), T790M-like, and exon 20 loop insertions) based on their influence on EGFR protein structure, as well as response to various types of EGFR-tyrosine kinase inhibitors (TKIs). However, the differences in molecular phenotypes and clinical outcomes for patients carrying these different forms of EGFR mutations are not fully understood. Here we sought to investigate the distribution of different EGFR structural types in Chinese NSCLC patients and the biological characteristics of each subgroup. Methods 2992 EGFR mutant NSCLC patients with available next-generation sequencing result were collected for mutation analysis. 118 patients with targeted RNA sequencing data were further analyzed to compare transcriptome differences across mutation subgroups. Results Across the entire cohort, 80.82% of patients were Classical-like, 5.92% were PACC, 10.76% were T790M-like, and 2.51% were Ex20ins. TP53 was the most common co-occurring mutation across the four subgroups, occurring in 60% of the T790M-like subgroup. Interestingly, the Ex20ins group exhibited a notable proportion of genomic alterations related to DNA repair processes. Additionally, both the Ex20ins and T790M subgroups demonstrated higher tumor mutational burden (TMB) scores. Furthermore, for the first time, we observed transcriptomic heterogeneity within these four subgroups. Classical-like group displayed enrichment of immune-related pathways, including PD1 signaling, CD28 family, and TCR signaling. Notably, the L858R group showed significant enrichment in immune activation signatures, including effector memory CD8 T cells, natural killer cells, and MHC I/II. This suggests a potentially robust immune response in that group. In contrast, the T790M-like subgroups showed lower anti-tumor immune signatures but were marked by a significant enrichment in tumor proliferation signatures. Conclusion In this study, we have employed a structure-based classification approach for EGFR mutants to comprehensively characterize the mutational landscape and heterogeneous biological traits at the transcriptional and functional levels in Chinese patients with NSCLC.